Prevalence and Risk Factors Associated with Potentially Inappropriate Prescribing According to STOPP-2 Criteria among Discharged Older Patients-An Observational Retrospective Study - Mariana Sipos; Andreea Farcas; Daniel Corneliu Leucuta; Noémi-Beátrix Bulik; Madalina Huruba; Dan Dumitrascu; Cristina Mogosan (MDPI AG, 2023)
Pharmacokinetic and pharmacodynamic changes associated with old age, along with multimorbidity and polypharmacy might lead to inappropriate prescribing and adverse reactions. Explicit criteria such as the Screening tool of older people's prescribing (STOPP) are useful to identify potential inappropriate prescribing's (PIPs). Our retrospective study included discharge papers from patients aged ≥65 years, from an internal medicine department in Romania (January-June 2018). A subset of the STOPP-2 criteria was used to assess the prevalence and characteristics of PIPs. Regression analysis was performed to evaluate the impact of associated risk factors (i.e., age, gender, polypharmacy and specific disease). Out of the 516 discharge papers analyzed, 417 were further assessed for PIPs. Patients' mean age was 75 years, 61.63% were female and 55.16% had at least one PIP, with 81.30% having one or two PIPs. Antithrombotic agents in patients with significant bleeding risk was the most prevalent PIP (23.98%), followed by the use of benzodiazepines (9.11%). Polypharmacy, extreme (>10 drugs) polypharmacy, hypertension and congestive heart failure were found as independent risk factors. PIP was prevalent and increased with (extreme) polypharmacy and specific cardiac disease. Comprehensive criteria like STOPP should be regularly used in clinical practice to identify PIPs to prevent potential harm.